Use of implantable cardioverter-defibrillators for primary prevention in older patients: A systematic literature review and meta-analysis - Melissa H. Kong; Sana M. Al‐Khatib; Gillian D Sanders; Vic Hasselblad; Eric D. Peterson (2011)
Randomized clinical trials (RCTs) have demonstrated the efficacy of implantable cardioverter-defibrillators (ICDs) in reducing sudden cardiac death (SCD) in specific patient populations. However, patients ≥ 65 years were under-represented in these trials and the overall benefit of ICDs may be diminished in older patients due to competing risks for death. We evaluate the published data on ICD efficacy at reducing all-cause mortality in patients ≥ 65 years and in patients ≥ 75 years.We searched MEDLINE to identify RCTs and observational studies of ICDs that provided age-based outcome data for primary prevention of SCD. The primary endpoint was mortality evaluated by a meta-analysis of the RCTs using a random-effects model. Secondary endpoints included operative mortality, long-term complications and quality of life.The enrollment of patients ≥ 65 years in RCTs was limited (range: 33% in DEFINITE to 56% in MUSTT). Combining data from four RCTs (n = 3,562) revealed that primary prevention ICD therapy is efficacious in reducing all-cause mortality in patients ≥ 65 years (HR 0.66; 95% CI 0.50-0.87; test of heterogeneity: X(2) = 5.26; p = 0.15). For patients ≥ 75 years, combining data from four RCTs (n = 579) revealed that primary prevention ICD therapy remains efficacious in reducing all-cause mortality (HR 0.73; 95% CI 0.51-0.974; p = 0.03). There appears to be no difference in ICD-related, operative, in-hospital, or long- -term complications among older patients compared to younger patients, although it remains unclear if older patients have a better quality of life with an ICD than younger patients.Although the overall evidence regarding ICD efficacy in patients ≥ 65 years is limited and divergent, and the evidence available for patients ≥ 75 years is even more sparse, our meta-analysis suggests that primary prevention ICDs may be beneficial in older patients. Our findings need to be validated by future studies, particularly ones examining ICD complications and quality of life.